THE POPULAR PROTECTION OF HUMAN RIGHTS DEFENDERS: Lessons learned in the Elma Novais case - Barbosa da Cunha, Luis Emmanuel (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2023)
Elma Novais case is an emblematic case for the creation of a formal/institutional methodology to protect human rights defenders. At the beginning of the 2000s, protection already existed for witnesses and children and adolescents, but for human rights defenders there was no adequate protection. The experience of popular protection was decisive to prove today how the Brazilian State’s first approach to protect Elma Novais was mistaken. The protection knowledge accumulated and systematized by Projeto Sementes is a historic brand of civil society.